Metrology, calibration, integration and testing of the WEAVE fibre positioner - Schallig, E (2019)
This thesis is about a pick-and-place fibre positioner for WEAVE, a new fibre-fed multi-object spectrograph for the 4.2 m William Herschel Telescope with a multiplex of 960. First light is expected sometime in 2020. The research presented in this thesis has been a major step in ensuring that the fibre positioner will be able to perform to the design specifications, and meet WEAVE’s scientific requirements.